Impact of COVID -19 in cancer patients on severity of disease and fatal outcomes: A systematic review and meta-analysis. Issue 5 (September 2020) - Salunke, Abhijeet Ashok; Nandy, Kunal; Pathak, Subodh Kumar; Shah, Jaymin; Kamani, Mayur; Kottakota, Viswanth; Thivari, Praveen; Pandey, Apurva; Patel, Keval; Rathod, Priyank; Bhatt, Supreet; Dave, Pariseema; et al.
Abstract: Background and aimsbackground: Currently there is limited knowledge on cancer and COVID-19; we conducted a systematic review and meta-analysis to evaluate the impact of cancer on serious events including ICU admission rate and mortality in COVID 19. Methods: PubMed, Cochrane Central Register of Clinical Trials were searched on April 16, 2020, to extract published articles that reported the outcomes of cancer in COVID-19 patients. The search terms were "coronavirus" and "clinical characteristics" with no language or time restrictions. We identified 512 published results and 13 studies were included in the analysis. Results: There were 3775 patients, of whom 63 (1·66%) had a cancer. The pooled estimates of ICU admission in COVID 19 patients with and without cancer were 40% versus 8·42%.The odds ratio of ICU admission rates between the cancer and non-cancer groups was 2.88 with a 95% CI of 1·18 to 7·01 (p = 0·026). The pooled estimates of death rate in COVID -19 patients with and without cancer were 20·83% versus 7·82%. The odds ratio of death rates between the cancer and non-cancer groups was 2.25 with a 95% CI ranging from 0·71 to 7·10 with p value of 0·166. The pooled prevalence of cancer patients was 2% (95 CI 1–4). Conclusions: Presence of cancer in COVID-19 leads to higher risk of developing serious events i.e. ICU admission, mechanical ventilation and mortality. The presence of cancer has a significant impact on mortality rate in COVID-19 patients. Highlights: COVID-19 in cancer patients is associated with higher morbidity. Patient with Comorbidities are likely to have higher risk of severe events. Cancer has a significant impact on ICU admission rate.